Walkthrough application of faculty of information and communications technologys building in the main campus and planner for the facilities inside the building - Rusnida, Romli; Shahrul Badariah, Mat Sah; Zulisman, Maksom (2006)
This paper suggests an alternative of visualizing non-existing information of permanent Fakulti Teknologi Maklumat dan Komunikasi's building (henceforth as FTMK) to the administrative personnel and other users. The main objective of this project is to develop a virtual walkthrough that could assist FTMK's administration in visualizing and planning the layout of the permanent campus of FTMK in Durian Tunggal, which is expected to be completed by the year 2008, into three-dimensional (3D) model. In order to achieve it, a walkthrough non-immersive virtual environment of the building is constructed which allows the user to navigate and interact with. the area. As it could be used as office planner, the walkthrough application will suggest some layout for lab, lecture hall, administration area and lecturer's room. This walkthrough application could also aid FTMK's staffs, students and communities to view the design of the building hence promoting FTMK and KUTKM.